The Utilization of Flashcards and Songs as Media for Introducing English Vocabulary at Mardisiwi Islamic Kindergarten - Millah, Hilyatul; Astuti, Wili (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to demonstrate the effectiveness of using flashcards and songs as media for introducing English vocabulary— specifically terms related to professions—to early‑childhood learners in Group A at Mardisiwi Islamic Kindergarten, and to analyze the factors that facilitate or hinder this vocabulary‑introduction process. Methodology: A mixed‑methods design was employed, involving eight Group A students, their teacher, and the school principal as participants. Data collection combined classroom observations, skill‑mastery checklists, semi‑structured interviews, and document analysis. For data analysis, the Miles and Huberman framework guided systematic coding, data reduction, and thematic synthesis to identify patterns of vocabulary acquisition and influencing factors. Results: Implementation of the flashcard‑and‑song intervention yielded clear gains in children’s mastery of profession‑related English terms. Sessions typically began with the teacher displaying a flashcard, inviting students to guess the depicted profession, and then revealing the English label while playing an accompanying song. Children demonstrated improved recall and active participation, indicating that the multimodal approach effectively reinforced word learning. Applications/Originality/Value: By combining visual and auditory stimuli in a structured yet playful format, this study offers a replicable model for early‑childhood English vocabulary instruction. Its identification of enablers (e.g., engaging media, supportive teacher guidance) and barriers (e.g., limited attention spans) can inform curriculum planners and kindergarten teachers in designing media‑rich lessons that optimize young learners’ language acquisition and maintain high engagement.